Amino Acid Composition of Some Conventional and Non-Conventional Leguminous Seeds - Sarjekar, Pushpalata; Shrivastava, S.K. (Asian Journal of Chemistry, 2010)
Some conventional (Glycine max variety Js-80-21 and Fava bean Jv-2) and non conventional (Albizia procera, Acacia auriculiformis and Peltophorum ferrugeneum) legumes were studied for their amino acid composition by amino acid analyzer.